2019
DOI: 10.1111/jgh.14611
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome and recurrence factors after percutaneous cholecystostomy as a definitive treatment for acute cholecystitis

Abstract: Background and Aim Percutaneous cholecystostomy (PC) has been frequently used as an alternative treatment for acute cholecystitis in seriously ill patients unfit for surgery. The aim of this study was to investigate the recurrence rate and risk factors of recurrence. Methods Medical records of 102 patients who were followed up for more than 1 year after PC tube removal among 716 patients who underwent PC for acute cholecystitis treatment were retrospectively analyzed. Results The recurrence rate of acute chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
(122 reference statements)
0
17
4
Order By: Relevance
“…In addition, an animal experiment revealed that biofilms on PC tubes could also contribute to another episode of cholecystitis (42,43). The clinical factors that could impact the recurrence of biliary disease have also been investigated, such as complicated cholecystitis, elevated CRP, and duration of PC catheter maintenance (28,37,44,45). All of this evidence supports interval cholecystectomy as the first choice after PC placement if the patients can tolerate surgery.…”
Section: Subsequent Management After Percutaneous Cholecystostomymentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, an animal experiment revealed that biofilms on PC tubes could also contribute to another episode of cholecystitis (42,43). The clinical factors that could impact the recurrence of biliary disease have also been investigated, such as complicated cholecystitis, elevated CRP, and duration of PC catheter maintenance (28,37,44,45). All of this evidence supports interval cholecystectomy as the first choice after PC placement if the patients can tolerate surgery.…”
Section: Subsequent Management After Percutaneous Cholecystostomymentioning
confidence: 99%
“…Prior to removing the PC tube, we suggest performing a clamping test. While there is no standardized clamping test, patients should be able to tolerate continuous clamping for at least 24-48 h (24,45,61). During the clamping period, there should be no symptoms and signs of recurrence; otherwise, the drainage tube cannot be removed.…”
Section: Pc Tube Removal Vs Pc Tube Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 102 patients with acute cholecystitis managed with percutaneous biliary drainage, Park and colleagues found an overall recurrence rate of 20.6% with median recurrence time of 660 d. In patients with cancer, the recurrence rate was 42.9%, with multivariate analysis revealing an odds ratio of 3.4 (95% CI, 1.0-11.28, P ¼ 0.05). 37 Cancer conferred a higher risk of recurrence with percutaneous drainage, but with a median recurrence time of more than a year, this may present a viable option for patients undergoing treatment for their malignancy or in the late stages of their disease. Endoscopic gallbladder drainage, whether it be retrograde cholangiography with transpapillary drainage (ETC) or ultrasound-guided cholecystostomy (EUSC), represents another therapeutic option for immediate source control in cholecystitis.…”
Section: Discussionmentioning
confidence: 99%